Trends in oral pathology of hunter-gatherers from Western Pampas, Argentina - Luna, Leandro Hernan (2014)
Oral health analysis is one of the principal bioarchaeological lines of investigation to evaluatethe interaction between the dynamics of human communities in the past, their environment, and theirsocial structure. These studies represent a relatively recent development in the study of native huntergatherersin Argentina. This paper focuses on oral pathology as a contribution to the understanding of thelifestyle diversity of these populations. A sample of human remains from the Chenque I site (WesternPampas, Central Argentina) was studied in order to identify differential patterns by sex, age-at-death,and location of the tooth in the arch. Six variables, considering both teeth and the alveolar tissue, wereexamined: caries, calculus, wear, periapical lesions, periodontal disease, and antemortem tooth loss. Theresults indicate that oral health deteriorated more in females. Some divergent patterns were also identifiedwhen compared with other contemporary bioarchaeological samples in the region. Both aspects areinterpreted in the context of previous proposals that consider the characteristics of hunter-gatherersdynamics just before the Spanish conquest.